The Influencce of Work Discipline and Incentives on Employee Performance at PT. Energi Cipta Utama - Islan Adi Stadiyanto; Zunaidah Zunaidah; Marlina Widiyanti; Agustina Hanafi (Jurnal Syntax Transformation, 2024)
This research was conducted with the aim of determining the influence of work discipline and incentives on employee performance at PT Energi Cipta Utama. The population in this study is all employees at PT Energi Cipta Utama consisting of supervisors, finance, admin, cashiers, operators and cleaning services at PT Energi Cipta Utama. In 2022, there will be 100 employees and all of them will be sampled using the census method in determining the sample. The results of multiple linear regression analysis show that work discipline and incentives have a positive and significant effect on employee performance. Work discipline at PT Energi Cipta Utama can be said to be good. This requires providing repeated and clear information to all employees, especially new employees regarding regulations and sanctions if they violate the regulations that have been implemented. Incentives, there needs to be an increase and evaluation of goods and supporting facilities that need to be renewed or added units so that employee work is not hampered.